THE INFLUENCE OF MOTIVATION AND WORKLOAD O EMPLOYEE PERFORMANCE IN PT. INTEGRA SYNERGY SERVICES - Angga Pratama; Abdul Somad (Asosiasi Dosen Muda Indonesia, 2024)
This study aims to determine the extent to which Motivation and Workload affect employee performance at PT Sinergi Integra Services (Tower Batavia Area, Central Jakarta) both partially and simultaneously. The research method used is quantitative descriptive which aims to describe the situation objectively by using numerical data collected through questionnaires. The sampling technique used is non-probability sampling with saturated sampling technique involving all 55 employees. Data analysis was carried out using the hypothesis testing method with the help of SPSS version 26 software. The results of the study indicate that Motivation and Workload have a significant influence on employee performance, both when tested partially and simultaneously. Based on the partial statistical test or t-test, it is known that Motivation significantly affects employee performance, while Workload is also proven to have a significant effect on employee performance. When tested simultaneously, the results show that Motivation and Workload together have a significant effect on employee performance. This indicates that the influence of Motivation and Workload on employee performance is 82.7%, while the rest, which is 17.3%, is influenced by other factors not included in the variables of this study.